Multimedia Software Development - Exploring The Solar System - Lau, Pung Wee (2002)
The developed encyclopedia-oriented multimedia software uses English Language as the main language. The main purpose of this project is to develop multimedia encyclopedia software in astrophysics to provide reference materials and attract people to study about astrophysics in order to increase their knowledge through the multimedia technology. The project target groups are the students ranging from the secondary to university levels and the public users. This project is very important just because our Malaysian Society are lack of knowledge about astrophysics and the problems in learning the astrophysics concepts could be reduced by using the multimedia technology. The various software's used to develop the multimedia software are Macromedia Director, Macromedia Flash, Adobe Photoshop, Photolmpact, Corel Draw, 3D Studio Max, Adobe Premiere and SoundForge. The developed multimedia software was made up of six basic parts: History Of Astronomy, Exploring The Sky, The Solar System, Astronomical Tools, Astronomical Quiz and Astronomical Experts. The developed multimedia software contains the animation, graphic. audio, video and text, which make the learning process more effective. This kind of multimedia-learning environment can improve the users understanding and prevent the misconception of astrophysics concepts. Hopefully, the developed multimedia software can serve as an interactive learning material to the Malaysian society to transform the Malaysian society into a knowledge-based society by the year 2020.